Therapeutic efficacy of ethanolic extract of Aerva javanica aerial parts in the amelioration of CCl4-induced hepatotoxicity and oxidative damage in rats - Ahmed H. Arbab; Mohammad K. Parvez; Mohammed S. Al-Dosari; Adnan J. Al-Rehaily; Khalid E. Ibrahim; Perwez Alam; Mansour S. Alsaid; Syed Rafatullah (Food & Nutrition Research, 2016)
Background: Liver diseases, the fifth most common cause of global death, can be metabolic, toxin-induced, or infective. Though approximately 35 Saudi medicinal plants are traditionally used to treat liver disorders, the hepatoprotective potential of Aerva javanica has not been explored. Objective: To investigate the antioxidative and hepatoprotective effect of Aerva javanica. Design: Total ethanol extract of A. javanica aerial parts was prepared and tested on DCFH-toxicated HepG2 cells ex vivo, and in CCl4-injured Wistar rats in vivo. MTT assay was used to determine cell viability and the serum biochemical markers of liver injury as well as histopathology was performed. In vitro 1,1-diphenyl-2-picrylhydrazyl and β-carotene free-radical scavenging assay and phytochemical screening of the extract were done. Furthermore, A. javanica total extract was standardized and validated by high-performance thin layer chromatographic method. Results: MTT assay showed that, while DCFH-injured cells were recovered to ~56.7% by 100 µg/ml of the extract, a 200 µg/ml dose resulted in hepatocytes recovery by ~90.2%. Oral administration of the extract (100 and 200 mg/kg.bw/day) significantly normalized the serum glutamate oxaloacetate transaminase, serum glutamate pyruvate transaminase, gamma-glutamyl transferase, alkaline phosphatase, bilirubin, cholesterol, high-density lipoprotein, low-density lipoprotein, very-low-density lipoprotein, triglyceride, and malondialdehyde levels, including tissue nonprotein sulfhydryl and total protein in CCl4-injured rats. In addition, the histopathology of dissected liver also revealed that A. javanica cured the tissue lesion compared to silymarin treatment. In vitro assays revealed strong free-radical scavenging ability of the extract and presence of alkaloids, flavonoids, tannins, sterols, and saponins where rutin, a well-known antioxidant flavonoid, was identified. Conclusions: Our findings demonstrate the potential of A. javanica in the attenuation of ex vivo and in vivo hepatotoxicity and oxidative damage. This further suggests its therapeutic value in various liver diseases. However, isolations of the active principles, their mechanisms of action, and other therapeutic contributions remain to be addressed.